ANALISIS KINERJA KEUANGAN UNTUK MENGUKUR TINGKAT KESEHATAN PADA BADAN USAHA MILIK DESA (BUMDes) RANTAU PANJANG CEMERLANG KECAMATAN KOTO GASIB KABUPATEN SIAK - Yuliana Sartika; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The level of financial health is the most important thing in the sustainability of a business entity, this is the background of this research. Good financial performance is the main factor in determining the level of health. This step was taken by the Village-Owned Enterprises (BUMDes) Rantau Panjang Cemerlang. This study aims to determine and analyze financial performance in measuring the level of health in Village Owned Enterprises (BUMDes) Rantau Panjang Cemerlang for the period 2017-2021. The method in this research is descriptive quantitative. The data analysis technique used is financial ratios. The ratios used in this study include liquidity ratios ( current ratio, quick ratio and cash ratio), solvency ratios ( debt to asset ratio and debt to equity ratio), activity ratios ( inventory turnover, working capital turnover and total asset turnover),and profitability ratios (gross profit margin, net profit margin, return on investment and return on equity). The results of this study indicate that the level of BUMDes liquidity is very large (overliquid). The level of solvency is very large, so the risk of BUMDes is also very large. The level of activity of BUMDes is not good and the level of profitability of BUMDes is also in poor condition. Keywords: BUMDes; Financial Performance; Financial Ratios and Health Level.